Postnatal care in Rwanda: facilitators and barriers to postnatal care attendance and recommendations to improve participation - Pamela Williams; Nathalie Kayiramirwa Murindahabi; Elizabeth Butrick; David Nzeyimana; Felix Sayinzoga; Bernard Ngabo; Angèle Musabyimana; Sabine F Musange (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Sub-Saharan Africa has the highest rates of neonatal mortality in the world with an estimated 1.2 million deaths within the first 28 days of life. Postnatal care (PNC) can contribute to reductions in morbidity and mortality in mothers and newborns through vital support that identifies danger signs and establishes valuable practices and referral processes. # Methods This qualitative data was collected as a part the East Africa Preterm Birth Initiative (PTBi-EA) to guide development of a group antenatal (ANC) and PNC model in Rwanda. Key-informant in-depth interviews (IDIs) and focus group discussions (FGDs) were conducted in four districts. Sixteen FGDs with 180 participants and 22 IDIs were completed at the time of thematic saturation. # Results Four themes highlighted facilitators and barriers to PNC attendance and recommendations to improve participation: 1) There is little awareness in the community of what the PNC package is; PNC 4 in particular is not well understood; 2) PNC visits by community health workers (CHWs) are well accepted and valued; 3) Providers perceive PNC 4 as an added burden to an already high workload; 4) Community structures exist to better disseminate key messages about PNC, but have not yet been effectively utilized. # Conclusions This qualitative work provides evidence that the PNC package was not initially well understood. Regardless, PNC service delivery performed by CHWs in Rwanda is well accepted and appreciated by the population, providing assurance that the full package has potential to be well utilized and valued by the population.